Implementation of Tahfidz Al Quran Learning Management in Improving the Quality of Tahfidz Al Quran and Tactile Learners at Junior High School : Implementasi Manajemen Pembelajaran Tahfidz Al Quran Dalam Meningkatkan Kualitas Tahfidz Al Quran Dan Tartil Peserta Didik di SMP - Iddris Iddris; Nur Efendi (Academia Open, 2021)
This research is expected to be able to find out in more details what problem are actually faced by the teachers of Al-qur’an. This study aims to determine the implementation of tahfidz Al-qur’an learning management in improving the quality tahfidz al-qur’an and tartil of the students. There are five components that are measured in this study, they are: planning, organizing, implementing, evaluating and the teachers role in carrying out thafidz and tartil learning activities. This implementation of this research used descriptive qualitative method. Researchers want to focus on finding out how the implementation, process, response, teacher’s role and evaluations are expected and sought. In this study of course hools. It is hoped that it will be able to provide spliyions to others quranic teachers but each research can give different result. During the implementation of the research, these obstacles must have included some children who memorized a lot but were weak in reading ability, there were children who were good at reading but weak in memorizing this could be due to different educational backgrounds. There were children who graduated from public and private elementary schools. This research is done in SMP Muhammadiyah 10 Sidoarjo. And the research subjects are: the headmaster, vice principal, tutor, administrative staff and some students. This research using qualitative descriptive method. And the data is collected by interviews, observation and documentation. From this research can be concluded that 1)tahfidz al-qur’an learning curriculum has not been implemented in the form of syllabus or RPP 2) tutor hasn’t created yet RPP but has already inform to the students what surah or juz must be memorized 3) the learning implementation is held outside of school hours 4) the evaluation activity is held in every the student memorize .